THE NEXUS BETWEEN AUDIT COMMITTEE ATTRIBUTES AND KEY AUDIT MATTERS: EVIDENCE FROM INSURANCE INDUSTRY - Adamu, Idris Adamu; Muhammad, Musa Musa; Teriyma, Orshi Samuel (Kashere Journal of Management Sciences, 2024)
Key audit matters (KAMs) are important for financial statement users as they provide clarity and in-depth understanding of financial statement audits. Empirical research on KAMs remains at an early stage particularly in Nigeria. Therefore, this study aims to investigate the effect of audit committee attributes on KAMs of the listed insurance companies in Nigeria. The study sample consists of 24 insurance companies from 2016-2022. The data for the study which was generated from annual reports and accounts of the insurance companies was analyzed using random effect regression. The findings show that audit committee independence and audit committee financial expertise have a negative and positive relationship with the number of KAMs respectively. Consequently, the result provides support on the agency problem between manager and shareholders. Based on result, the study recommends that regulatory bodies such as the National Insurance Commission (NAICOM) should continue to engage the insurance companies in the area of good corporate governance practices. This will go a long way in mitigating non-disclosure of vital information in the financial statements. Furthermore, the implication of this issue is that the financial statements cannot be relied for informed decision making